A análise linguística no discurso de professores do ensino básico: conflitos e silenciamentos - Silva, Oziel Pereira da (2018)
This investigation seeks to understand how the teacher builds his speech before the demands of PCN about practice of Linguistic Analysis [AL], a fresh proposal for the study / teaching of grammar contents that directs the student to reflect on the role and the (s) direction (s) the linguistic resources used in the texts, in order to develop their linguistic and discursive skills. Soon, it is not only based linguistic analysis and / or extracting text phrases, sentences and times descontextualise employees, as in the traditional model of teaching grammar, but producing a reflection of activity on the language as a whole [epilinguística activity] addressing the many aspects that make it up - including, pragmatic and semantic - and to relate to the specific practices of the subjects in actual dialogue. The main purpose of this research, therefore, is to comprehend the teacher's imagination concerning the new claims on the management of language guided by the PCN and present theories of teaching grammar. The methodological trajectory guided up by qualitative principles, and the theoretical happened under interdisciplinary bases, realized by dialogue between Applied Linguistics and the French Discourse Analysis (PÊCHEUX, 1990, 1997a, 1997b, 2008; ORLANDI, 1994, 1995, 2002, 2005), three (03) teachers of the 1st, 2nd and 3rd High School series, in a state school in the municipality of Conceição do Araguaia-PA. Was utilized as instruments to generate the data: (i) questionnaire and (ii) semi-structured interviews. The results point to a partial understanding of the AL, by the teachers, which, for us, is significant, since imply potential traversing movements in relation to the normative-prescriptive teaching [reflective subjection], probably because of contact you had, in initial training, with the contemporary speeches on the portuguese language teaching.